A solidariedade afetiva como fundamento ético : Husserl e a renovação no mundo da vida - Erthal, Cesar Augusto (2017)
The present Doctorate thesis, entitled AFETIVE SOLIDARITY AS AN ETHICAL BASIS: HUSSERL AND RENEWAL IN THE WORLD OF LIFE, the result of a bibliographical research based on the work of Edmund Husserl and his commentators, aims to reflect on the theme of the crisis of the ethical values in the present time from the last writings of the philosopher. We will argue that affective solidarity through the ideas of Empathy (Einfühlung) and "love of next" is presented as the foundation of intersubjective relations and renewal of the crisis of ethical values in the world of life. This affective solidarity will seek to be a safe haven in a world that is experiencing the increase of intolerance, of social insensitivity and, therefore, the lack of a collective and participatory ethics. Husserl, in the articles for the Japanese magazine Kaizo presents indicatives that we consider essential to investigate when defending the idea of affective solidarity, since the philosopher refers to the social acts that occur through the community life where the subjects cooperate with forces united to each other. In the Husserlian proposal for the value of life, the value of the world, indicating the necessary unification of one's life with one another, thus unifying itself in a community life, offers us a foundation in the defense of this thesis, since a life that is intertwined in the struggle for Common good may in the end be a renewed ethical life. We will try to understand the proper method of phenomenology which, being a conception of science and philosophy, is a way or procedure to reach a knowledge of rigor. Thus, from an analysis of Husserl's work, describe a proposed thesis meaning a leap of rebirth with philosophy in a time of crisis of ethical values. Therefore, studying and analyzing, trying to understand the idea of a crisis in focus, is trying to demonstrate not a desperation in front of the established framework, but a challenge, a struggle for hope, an overcoming or renewal of people in the construction of humanity.